Pseudoaneurysm as a devastating complication of pancreatic pseudocyst following pheochromocytoma resection - Jasper Williams; Andrea P. Dutoit; Rachel A. Spitznagel; Brian Jones; Lincoln Wong; Michelle M. LeRiger (Elsevier, 2020)
Pancreatic pseudocysts are uncommon complications of pancreatic injury in the pediatric population. A rare but devastating complication of pseudocyst development is pseudoaneurysm formation. We report the case of a 13-year-old patient with a pheochromocytoma who developed a pancreatic pseudocyst postoperatively with subsequent catastrophic bleeding from an undetected pseudoaneurysm rupture. The patient underwent emergent exploratory laparotomy requiring initiation of the massive transfusion protocol followed by multiple reoperations. This case illustrates the potential consequences of an unrecognized pseudoaneurysm. Although in this case there were no symptoms prior to hemodynamic instability, other cases may demonstrate signs or symptoms that should not be ignored.